Analysis Of The Internal Control System In Preventing Arrears Of Accounts Receivable At PT Aneka Gas Industri Medan - Nurlia Azizah; Heriyati Chrisna; Nina Andriany Nasution (International Journal of Management, Economic and Accounting, 2025)
This study aims to determine how internal control is implemented in preventing accounts receivable arrears at PT. Aneka Gas Industri Medan, how the company assesses the risk in providing accounts receivable, and how effective monitoring of accounts receivable arrears is. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The theory used as the basis for the analysis is the internal control framework according to COSO (Committee of Sponsoring Organizations of the Treadway Commission). The results of the study indicate that PT. Aneka Gas Industri Medan has implemented an adequate internal control system. Authorization procedures are carried out by authorized officials, segregation of duties has been implemented properly, and transaction documentation is carried out in an orderly manner through a computerized system. Risk assessment is carried out through an analysis of customer eligibility before granting credit, including considering the customer's payment history and financial condition. Monitoring of accounts receivable is carried out periodically through the accounts receivable aging report (Aging Schedule) and routine evaluations by management. Although control has been running quite effectively, the company still needs to strengthen the credit evaluation policy and optimize the monitoring system to be more responsive. By implementing structured internal control, the company is able to minimize the risk of bad debts and maintain the stability of operational cash flow.